2020
DOI: 10.1002/wcs.1528
|View full text |Cite
|
Sign up to set email alerts
|

Is atypical rhythm a risk factor for developmental speech and language disorders?

Abstract: Although a growing literature points to substantial variation in speech/language abilities related to individual differences in musical abilities, mainstream models of communication sciences and disorders have not yet incorporated these individual differences into childhood speech/language development. This article reviews three sources of evidence in a comprehensive body of research aligning with three main themes: (a) associations between musical rhythm and speech/language processing, (b) musical rhythm in c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
164
2
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
2

Relationship

2
7

Authors

Journals

citations
Cited by 146 publications
(180 citation statements)
references
References 334 publications
(428 reference statements)
11
164
2
3
Order By: Relevance
“…Importantly for our study, several recent studies suggest that rhythm processing is also impaired in DLD (Alcock, Passingham, Watkins & Vargha-Khadem, 2000;Corriveau & Goswami, 2009;Corriveau et al, 2007, Cumming et al, 2015, and this might contribute to the linguistic problems due to the shared underlying mechanisms between rhythm and speech processing discussed above. Weaker rhythm processing in children with DLD is also in line with the Atypical Rhythm Risk Hypothesis that posits that individuals with atypical rhythm are at higher risk for speech/language disorders (Ladányi, Persici, Fiveash, Tillmann & Gordon, 2020). Goswami (2011) proposed the temporal sampling (oscillatory) model, a theory motivated by the Dynamic Attending Theory (Large & Jones, 1999), to account for language problems primarily in children with dyslexia and, by extension, also for DLD.…”
Section: Developmental Language Disordermentioning
confidence: 71%
“…Importantly for our study, several recent studies suggest that rhythm processing is also impaired in DLD (Alcock, Passingham, Watkins & Vargha-Khadem, 2000;Corriveau & Goswami, 2009;Corriveau et al, 2007, Cumming et al, 2015, and this might contribute to the linguistic problems due to the shared underlying mechanisms between rhythm and speech processing discussed above. Weaker rhythm processing in children with DLD is also in line with the Atypical Rhythm Risk Hypothesis that posits that individuals with atypical rhythm are at higher risk for speech/language disorders (Ladányi, Persici, Fiveash, Tillmann & Gordon, 2020). Goswami (2011) proposed the temporal sampling (oscillatory) model, a theory motivated by the Dynamic Attending Theory (Large & Jones, 1999), to account for language problems primarily in children with dyslexia and, by extension, also for DLD.…”
Section: Developmental Language Disordermentioning
confidence: 71%
“…Once we have acquired the language successfully, this feature may be less relevant to successful speech perception. Given the observations that some developmental language disorders, such as dyslexia, may be associated with impaired sensitivity to syllable stress [10][11][12] , future directions may examine this MMN (in)sensitivity in children and adults with dyslexia. www.nature.com/scientificreports www.nature.com/scientificreports/ ERP responses to formal and temporal deviants both suggest that the probability of occurrence within a language has an impact on how we process speech, with more probable constructions being processed more readily.…”
Section: Discussionmentioning
confidence: 99%
“…A few studies have found variation in metre to influence semantic 8 and syntactic 9 processing. Furthermore, difficulties in processing the temporal structure of speech have been suggested to underlie phonological processing deficits observed in dyslexia [10][11][12] . It is therefore of interest to study how formal and temporal predictability may interactively influence speech perception.…”
mentioning
confidence: 99%
“…Potential downstream effects of general rhythmic processing skills on higher-order linguistic abilities are currently being extensively investigated, particularly in the context of first language acquisition (for a recent review, see [24]). Accordingly, several studies in this Special Issue probe whether the acoustic properties of speech rhythm can serve as scaffolding for the acquisition of stable phonological representations [12], for the segmentation of words from continuous speech and the construction of lexical representations [13], for the recognition of syntactic units in sentences [10] and for reading [7,8,11].…”
mentioning
confidence: 99%